A multidimensional review of the applications and implications of quantum dots in modern agriculture - Wan Azamuddin, Wan Nur Zarifah; Abdullah, Janna Ong; Mohamad Azzeme, Azzreena; Abd Gani, Shafinaz; Mohamad, Rosfarizan; Halim, Murni; Wasoh, Helmi; M. Sobri, Zulfazli (Discover, 2025)
Quantum dots (QDs) are nanoscale materials exhibiting quantum confinement effects synthesized from various sources, including semiconductors QDs (e.g., CdSe, PbS), carbon-based materials, MXenes, magnetic QDs, metal oxides, chalcogenides, and perovskites that have unique optical and electronic properties, typically ranging from 1 to 10 nanometers. These properties, including tunable fluorescence, high photostability, and size-dependent emission that greatly influenced by the size, shape, and composition of QDs. Due to their small size, QDs exhibit a high surface-to-volume ratio, where quantum confinement dominates and results in a size-dependent bandgap unlike other bulk materials. Its nanosructure composed of core-shell configurations with specific bandgap alignments such asType-I or Type-II, between the valence band critically influence their optical and electronic properties. QDs are synthesized using either top-down or bottom-up approaches, depending on the desired structure and properties. These synthesis techniques allow for precise control over the size, composition, and functionality of QDs. The QDs evolve in agricultural practices especially semiconductor QDs and carbon quantum dot (CQD) that have significant effects, increased crop yields by 15–40%, enhanced photosynthesis by 56%, and boosted nitrogen uptake by 30%. They help plants tolerate stress by improving root health and water efficiency, aiding sustainable crop production. However, their successful application depends on understanding their uptake mechanisms in plants and addressing concerns related to their toxicity and environmental impact. This review explores the synthesis, applications, and potential risks associated with QDs in agriculture, highlighting their role in advancing sustainable agricultural practices.